Prevalence and significance of fluoroquinolone-resistant bacteria carriage in patients undergoing transrectal ultrasound prostate biopsy - Hasanzadeh, Amir; Pourmand, Mohammad Reza; Alizadeh, Ahad; Pourmand, Gholamreza (Urology Journal, 2017)
Purpose: To determine the prevalence of fluoroquinolone-resistant (FQR) bacteria carriage in patients undergoing transrectal ultrasound prostate biopsy (TRUS-Bx), and the relationship between the risk factors and FQR carriers as well as infections after prostate biopsy. Materials and Methods: Rectal swabs were obtained from 158 patients undergoing TRUS-Bx. The FQR organisms were isolated using selective media, and the antibiotic susceptibility pattern was determined. Moreover, after prostate biopsy, blood and urine samples were collected from patients with post-biopsy infection (PBI) during 30 days of follow up. Results: In total, 73 (46.2%) patients were positive for ciprofloxacin-resistant bacteria in rectal cultures. The most dominant isolates were Escherichia coli (95.9%). The antibiotic susceptibility patterns for the FQR rectal and clinical isolates showed high levels of resistance to ampicillin (94%) and trimethoprim-sulfamethoxazole (89.5%), while the resistance to amikacin, fosfomycin and imipenem remained very low. The multivariate analysis showed that previous use of FQs (OR, 2.54; 95% CI, 1.17-5.49; P = .019) and history of hospitalization (OR, 7.85; 95% CI, 2.075-29.744; P = .002) were significantly risk factors for the FQR carriage. On the other hand, the risk of PBI was higher among intestinal carriers of fluoroquinolone resistant bacteria compared with noncarriers, that this difference was statistically significant (24% versus 3.5%, P < .001).The rates of PBI and hospitalization after TRUS-Bx were 12.5%, and 4.43%, respectively. Conclusion: An increase in the rectal FQR bacteria carriage is associated with elevated PBI, which strongly recommends the need for an appropriate prophylaxis to reduce infections in patients undergoing TRUS-Bx.